Coral bioerosion on the marginal reefs of northeastern Arabia. Issue 2 (2nd April 2020) - Al-Mansoori, Noura; McParland, Dain; Howells, Emily; Bauman, Andrew; Burt, John A.
Abstract : The maintenance of coral reef framework results from a balance between skeletal accretion and bioerosion, and this balance can be disrupted by environmental stress and disturbance. Coral reefs in northeastern Arabia exist in extreme environmental conditions and have experienced severe disturbances in recent years. This study assessed the intensity of macrobioerosion in two regionally common species, Platygyra daedalea and Cyphastrea microphthalma, at three sites within the southern Persian/Arabian Gulf and at one site in the Sea of Oman. On average, bioeroders removed 9.2 ± 1.6% of the skeletal surface area in P. daedalea and 26.4 ± 1.6% in C. microphthalma, with variation between species attributed to differences in colony morphology. Bioerosion intensity varied among sites in each species. Within the southern Arabian Gulf, both P. daedalea and C. microphthalma showed the highest bioerosion intensity at Delma, in the western region, compared with that of Saadiyat or Ras Ghanada to the east, with the elevated bioerosion at Delma consistent with a history of more extreme environmental conditions and bleaching-related disturbances. The highest bioerosion in P. daedalea occurred at Fujairah in the Sea of Oman, and this site was amongst the highest in C. microphthalma . Although this site is characterized by more benign environmental conditions, reefs in this area experienced mass coral mortality due to anoxia during a large-scale harmful algal bloom in 2008/9 and the high bioerosion in Fujairah likely represents a long-term signature of this disturbance. The intensity of macrobioerosion observed here is high compared with other regions, suggesting that that chronic exposure to long-term environmental stress and a history of disturbance may lead enhanced loss of reef framework.